A practical-theological perspective on corruption: towards a solution-based approach in practice - W. Coetzer; L. E. Snell (Acta Theologica)
This article aims to delineate the basis-theoretical and meta-theoretical perspectives on the phenomenon of corruption. It defines solution-based pastoral markers should the research indeed establish a definitive role for pastoral theology in addressing this serious societal ill. Thus it attempts to scrutinize the dynamic factors associated with the phenomenon of corruption in general and as it pertains to South Africa. It also examines the views of both Scripture and related disciplines on corruption, then compare some of the current solutions proposed in the literature on dealing with it. Furthermore, it determines and practically delineate the role and parameters of practical theology in an attempt to address the issue of corruption. Finally, one of the following hypotheses is accepted: Firstly, Practical Theology has a distinct role to conduct in rooting out corruption within society. Secondly, Practical Theology has no defined role in assisting with the eradication of corruption within society.